2018
DOI: 10.1016/j.devcel.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

PAF-Myc-Controlled Cell Stemness Is Required for Intestinal Regeneration and Tumorigenesis

Abstract: The underlying mechanisms of how self-renewing cells are controlled in regenerating tissues and cancer remain ambiguous. PCNA-associated factor (PAF) modulates DNA repair via PCNA. Also, PAF hyperactivates Wnt/β-catenin signaling independently of PCNA interaction. We found that PAF is expressed in intestinal stem and progenitor cells (ISCs and IPCs) and markedly upregulated during intestinal regeneration and tumorigenesis. Whereas PAF is dispensable for intestinal homeostasis, upon radiation injury, genetic ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 67 publications
2
32
0
Order By: Relevance
“…Myc also functions as an oncogene, contributing to both tumor initiation and maintenance by controlling cell growth [27]. A recent study has shown that c-Myc activation positively regulates cell self-renewing and is indispensable for crypt regeneration and colon tumorigenesis [28]. Of interest, a domain-based interaction resource suggested a binding between human Myc and SCD1 proteins [29].…”
Section: Discussionmentioning
confidence: 99%
“…Myc also functions as an oncogene, contributing to both tumor initiation and maintenance by controlling cell growth [27]. A recent study has shown that c-Myc activation positively regulates cell self-renewing and is indispensable for crypt regeneration and colon tumorigenesis [28]. Of interest, a domain-based interaction resource suggested a binding between human Myc and SCD1 proteins [29].…”
Section: Discussionmentioning
confidence: 99%
“…The β-catenin paradox Wnt signaling hyperactivation by mutations in β-catenin destruction complex components or β-catenin itself contributes to tumorigenesis. In addition to APC mutations, β-catenin can be further activated by additional layers of regulation 39,40,[111][112][113][114][115][116][117] , which demonstrated the complexity of Wnt signaling deregulation in cancer. Accumulating evidence supports the notion that additional regulatory processes contribute to Wnt signaling hyperactivation in cancer, as demonstrated in the following examples.…”
Section: Additional Layers Of Wnt/β-catenin Signaling Activationmentioning
confidence: 99%
“…Additional work has highlighted the role of the Myc pathway in controlling proliferation of intestinal crypt stem cells, acting as an important transcriptional target of Wnt/b-catenin signaling, and translating the activity of this pathway into the control of cell division. [38][39][40] This is supported by studies showing that the absence of the cofactors required for Myc expression in crypt stem cells impairs their capacity for regeneration in vivo. [38][39][40] Furthermore, analysis of apoptosis components within intestinal tissues across mouse and human revealed that high expression of antiapoptotic Bcl-2 is restricted predominantly to the Lgr5 + stem cells of the crypt base, and expression falls gradually as cells progress toward the villus tip.…”
Section: Further Analogs: Autonomous Organoid Aggregationmentioning
confidence: 88%
“…[38][39][40] This is supported by studies showing that the absence of the cofactors required for Myc expression in crypt stem cells impairs their capacity for regeneration in vivo. [38][39][40] Furthermore, analysis of apoptosis components within intestinal tissues across mouse and human revealed that high expression of antiapoptotic Bcl-2 is restricted predominantly to the Lgr5 + stem cells of the crypt base, and expression falls gradually as cells progress toward the villus tip. 41 This raises the potential for a timed loss of antiapoptotic molecule expression as cells mature, ultimately resulting in their programmed death after their terminal differentiation into enterocytes at the villus tip.…”
Section: Further Analogs: Autonomous Organoid Aggregationmentioning
confidence: 88%